Impact of Earnings Management Practices on Stock Return - Bhutto, Niaz Ahmed; Shaique, Muhammad; Kanwal, Sahar; Matlani, Anjlee (UI Scholars Hub, 2021)
This paper investigates the impact of earnings management (real and accrual) on stock returns ofPakistan stock exchange (PSX) listed companies. The study is done by testing a separate relationship of accrual and real earnings management and their collective relationship with the stock return. The study is conducted on 3900 firm-year observations from the non-financial PSX listed companies for the sample period 2005-17. The findings of the study show that a significant and negative relationship exists between stock returns and real and accrual earnings management. Moreover, the combined impact of real and accrual earnings management on stock return is also found to be significantly negative. This paper could prove a valuable addition to the knowledge of investors because investors can more or less price accrual earning management.